Blood Cell Membrane Fluidity and Intracellular Ca2+ Changes in Antiretroviral-Naïve and -Treated HIV-1–Infected Patients. (2010) - Santos, Nuno C.; Martins e Silva, J.; Freitas, Teresa; Doroana, M.; Duarte, N.; Tavares, L.; Antunes, F.; Saldanha, Carlota
Abstract : We previously showed that lymphocytes and erythrocytes of HIV-1–infected patients, prior to antiretroviral therapy, presented significant changes in intracellular calcium concentration ([Ca 2+ ]int ) and membrane fluidity. The present study evaluates the same parameters after response to highly active antiretroviral therapy (HAART). Blood samples were collected from patients prior to and after antiretroviral therapy, and from control subjects. Membrane fluidity and [Ca 2+ ]int were assessed by fluorescence spectroscopy measurements, using three different probes: TMA-DPH and DPH for membrane fluidity, and fura-2 for Ca 2+ . When compared with the control group, both untreated and treated patients presented increased lymphocyte [Ca 2+ ]int and decreased lymphocyte membrane fluidity, without significant differences between the two groups of patients. On the contrary, the therapy reversed the membrane fluidity variations observed in erythrocytes. The decreased erythrocyte [Ca 2+ ]int of untreated patients was not reversed by HAART. AIDS patients present changes in lymphocyte (mostly noninfected) and erythrocyte properties, partially reversed by HAART, consistent with a process of facilitated propagation of the infection to new cells, stimulation of virion production, and maintenance of a reservoir of erythrocyte-bound infectious virus. These observations can be related with the action of the HIV Nef protein in the cell's proteins and lipid composition, as well as with the recently observed cell infection by HIV-1 via endocytosis.